Post Disaster Students’ Mental Spirituality Development at Government Junior High Schools in Palu - Muhammad Abdul Razak; Saefuddin Saefuddin; Ruslin Ruslin (Department of Islamic Education, Postgraduate Program State Institute for Islamic Studies Palu, 2021)
This study discusses teachers strategy to improve students mental sorituality after natural disasters at a junir high school in Palu city. This study was conducted to help students to recover their mental spirituality after experienced traumatic natural disasters. In conducting the study, we used a qualitative case study method. The case of this study was a stateb junior high school in Palu city. Data were gathered through direct field observation, in-depth interviews which involve teachers and the school principle. We also analyzed written material, such as the school teaching activities, to understand how the teachers at the school helped students to recover their mental spirituality during post disasters period. Our study found that teachers has been able to carry out mental and spiritual recovery of the students after the natural disaster in Palu. The students who were initially lazy to participate in religious activities became diligent. Then the students who initially rarely prayed became diligent to pray. The teachers awaken students' awareness of the importance of maintaining spirituality after experiencing a disaster through various religious activities in the school environment